2015
DOI: 10.1093/aob/mcv139
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory ecological factors for the persistence of desiccation-sensitive seeds in transient soil seed banks:Quercus ilexas a case study

Abstract: This study provides part of the knowledge required to implement species distribution models which incorporate their regeneration niche. It is an important step forward in evaluating the ecological consequences of increasing winter drought and environmental filtering due to climate change on the regeneration of the most dominant Mediterranean tree species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…Hill, Edwards & Franks ; Joët et al . ). Here, we included both woody and herbaceous species in our calculations and, in an analogous habitat (tropical and sub‐tropical moist broadleaf forest), found that the proportion of all seed plants with desiccation‐sensitive seeds was just 18·5%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hill, Edwards & Franks ; Joët et al . ). Here, we included both woody and herbaceous species in our calculations and, in an analogous habitat (tropical and sub‐tropical moist broadleaf forest), found that the proportion of all seed plants with desiccation‐sensitive seeds was just 18·5%.…”
Section: Discussionmentioning
confidence: 97%
“…For Q. ilex (Fagaceae), a dominant canopy tree in temperate European forests, a clear relationship has been found between winter cumulative rainfall and seed water content (Joët et al . ). The authors then demonstrated that a winter with exceptional periods of drought led to high seed mortality within the species’ range in France, providing clear evidence that increases in droughts are likely to have a significant impact on the regeneration of this species which, like other members of its genus, produces desiccation‐sensitive seeds.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Edaphic drought due to precipitation reduction is known to prevent or limit the success of Q. ilex seedling recruitment at two important stages. First, acorns being desiccation-sensitive seeds, they may lose their ability to germinate if they dehydrate during winter dry spells [33]. Second, summer drought episodes that are characteristic of the Mediterranean climate, impose severe plant water stress that can be readily lethal to young seedlings [12].…”
Section: Discussionmentioning
confidence: 99%
“…DS seeds can maintain their high water content due to their commonly large size which results in a large water reservoir, the loss of this being minimized by canopy shading (Joët et al 2016). The increased seed size also results in an increased accumulation of storage reserves.…”
Section: Ecological Aspects Of Desiccation-sensitive Seedsmentioning
confidence: 99%